Alterações químicas e microbiológicas do solo decorrentes da adição de cinza de casca de arroz. - Sandrini, Wilian Costa (2010)
The use of rice husk (RH) as an alternative source of energy generation, produces a high amount of residual ash that is deposited in the environment inappropriately. Researches related to proper use of rice husk ash (RHA) are required for the search for sustainable alternatives to avoid contamination and / or environmental pollution. Thus, the objective of this work was to evaluate the effects of application of rice husk ash on the growth of corn and also on some chemical and microbiological Albaqualf. The experiment was conducted in two stages, the first in a greenhouse in the experimental area of the Soils Department, Eliseu Maciel Agronomy College, Federal University of Pelotas (UFPEL), Capão do Leão, RS, during the period January to March 2009. The studied treatments were: T1 control (0,0 g kg-1 RHA); T2 mineral fertilization NPK + lime; T3 1,09 g kg-1 RHA; T4 2,17 g kg-1 RHA; T5 4,34 g kg-1 RHA; T6 6,51 g kg-1 RHA; T7 8,68 g kg-1 RHA. In this stage were evaluated the growth and the levels of some nutrients in plants and the change in some chemical and microbiological soil. The second stage was developed in Microbiology Laboratory of the soil, using respirometric vessels, with the same soil and treatments of previous stage, for the analysis of soil basal respiration. The experimental design was completely randomized with four replications. The application of RHA increased the yield of dry mass of maize, as well as the values of pH, electric conductivity and the levels of P, Na, Si in the soil, providing also a decrease on the levels of the Fe and Al of the soil and of maize plants. The doses of rice husk ash did not affect microbial biomass measured by the carbon and nitrogen microbial. The soil microbial activity, the metabolic quotient and the relation microbial biomass carbon / total organic carbon of the soil also did not change with the application of waste.